Investigating Anxiety and Fear of COVID-19 as Predictors of Internet Addiction With the Mediating Role of Self-Compassion and Cognitive Emotion Regulation - Moniri, Reihaneh; Pahlevani Nezhad, Kimia; Lavasani, Fahimeh Fathali (Frontiers in Psychiatry, 2022)
Background In addition to many deaths due to the Coronavirus pandemic, many psychological issues and problems are affecting people's health. Including the constant anxiety and fear of infecting themselves and their families, COVID-19 has led to excessive spending of time in cyberspace and the Internet. Methods In this study, the role of fear and anxiety of COVID-19 in predicting Internet addiction among 1,008 students was investigated. The mediating role of the two components of self-compassion and cognitive emotion regulation has also been measured. Data collection was done online due to the outbreak of the disease and a modeling method was used to analyze the data. Results The results shows that anxiety and fear of COVID-19 has a positive and significant relationship with both Internet addiction (r = 0.32) and maladaptive cognitive emotion regulation strategies (r = 0.17), and it has a negative relationship with self-compassion (r = −0.25). Conclusions The findings suggest that self-compassion can play a protective role against internet addiction at the time of COVID-19 pandemic while maladaptive strategies for emotion regulation can be risk factors for anxiety and fear of the virus.